2017
DOI: 10.1080/13880209.2017.1282969
|View full text |Cite
|
Sign up to set email alerts
|

Antimutagenic and anticlastogenic effects of Turkish Black Tea on TA98 and TA100 strains of Salmonella typhimurium ( in vitro ) and mice ( in vivo )

Abstract: Context: Black tea has been reported to have significant antimutagenic and anticarcinogenic properties associated with its polyphenols theaflavins (TF) and thearubigins (TR). Similarly, Turkish black tea (TBT) also contains a considerable amount of TF and TR.Objective: This study investigated the mutagenic, antimutagenic and anticlastogenic properties of TBT.Materials and methods: The mutagenic and antimutagenic effects of TBT (10 to 40000 μg/plate) were investigated in vitro on Salmonella strains TA98 and TA1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 25 publications
3
11
0
Order By: Relevance
“…This results showed that inhibition of mutagenic substrates, which needs metabolic activation, such as 2-AA and 2-AF in our study can be attributed to inhibition of cytochrome P450 isoenzymes. Also Charehsaz et al [41] and Mocan et al [42] indicated that protective effects of plant extracts increased in the presence of S9 metabolic activation system by inhibiting cytochrome P450 monooxygenases.…”
Section: Discussionmentioning
confidence: 98%
“…This results showed that inhibition of mutagenic substrates, which needs metabolic activation, such as 2-AA and 2-AF in our study can be attributed to inhibition of cytochrome P450 isoenzymes. Also Charehsaz et al [41] and Mocan et al [42] indicated that protective effects of plant extracts increased in the presence of S9 metabolic activation system by inhibiting cytochrome P450 monooxygenases.…”
Section: Discussionmentioning
confidence: 98%
“…This could be due to an interaction with the genotoxic agents. However, when we tested different times between HRCHs and the alkylating agent, the anticlastogenic effect is maintained by HRCH 7 similar to various phytochemicals [ 62 65 , 67 70 ]. Oxidative stress, chronic inflammation, and genomic instability events are predisposing factors for neoplastic transformation [ 71 73 ], and perturbation of these events may interfere with the malignant progression of cells.…”
Section: Discussionmentioning
confidence: 99%
“…The number of revertant colonies grown on plates containing AFB1 without NSO and NDO was defined as 100 %, which means 0 % inhibition. The percentage of inhibition was calculated according to the method described previously [38] . The antimutagenic effect was considered moderate and strong when the inhibitory effects were 25–40 % and more than 40 %, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The percentage of inhibition was calculated according to the method described previously. [38] The antimutagenic effect was considered moderate and strong when the inhibitory effects were 25 -40 % and more than 40 %, respectively. Inhibitory effect less than 25 % was considered as weak and was not recognized as a positive result.…”
Section: Assessment Of In Vitro Antioxidant Potential 22-diphenylpicrylhydrazyl (Dpph) Radical-scavenging Activitymentioning
confidence: 99%
See 1 more Smart Citation